DEVELOPMENT OF ELECTRONIC STUDENT WORKSHEETS THROUGH NATURAL SCIENCE PROJECT-BASED LEARNING IN ELEMENTARY SCHOOL - Virdayanti Virdayanti; Herlina Usman; Juhana Sakmal (EDUTECH, 2022)
This research aims to produce project-based learning-based electronic learner worksheets as a support for natural science learning materials in the fifth grade of elementary school. Methods used by Research Development using an approach developed using; Analyze, Design, Develop, Implementation, and Evaluation (ADDIE). This research was held at Munjul State Elementary School 01 East Jakarta. The steps in this study are 1) Conducting needs analysis through interviews and questionnaires, 2) Making product designs, 3) Conducting product development, 4) Conducting trials to learners and 5) Evaluating products. The object in the study was 30 elementary school fifth graders, data analysis techniques using interviews and questionnaires. The results of the development trial were evaluated by media experts 88.5% material experts 84.61% and linguists obtained from an average score of 92.3% with excellent categories, then the results of product trials through one to one got a score of 83.75% with excellent categories and product trial results through small groups got a score of 88.33 % with very good category. This research shows that project-based learning-based electronic learner worksheets are feasible to be used for learning media as an additional source of fifth-grade elementary school natural science learning.